FAKTOR PENGHAMBAT IMPLEMENTASI RESOLUSI DEWAN KEAMANAN PBB DALAM MENYELESAIKAN MASALAH PEMUKIMAN ILEGAL DI PALESTINA - Cici Malinda Sari; Saiman Pakpahan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study talks about the issue of illegal settlements in the Palestinian territories. The illegal settlements built by Israel in the Palestinian territories have sparked opposition from various countries and violated international law because it is located on the streets or areas that are not part of Israel but the Palestinian territories. The UN Security Council made a resolution on the issue of illegal settlements, in the implementation there are several obstacles that cause the failure of peace in the creation of Palestine.Various kinds of peace efforts have been made to create peace on the earth of Palestine. All peace talks and agreements have been signed, but the deal has run aground. All agreements and resolutions are still being violated by Israel, the offense was caused by some principal issues between the two sides. But the Israeli side always wins in the wind in various situations and conditions, so Israel is always on the side who always benefit, while the Palestinians are always on the side of the disadvantaged. Israel has a power that is strong enough so that superpowers like the US even on Israel.The failure or stalled negotiations of agreement and peace are the result of many inhibiting factors even though the UN Security Council has sought to make a resolution for the creation of peace or the ever-initiated solution of a two-state solution. Whether the barriers from within and from outside. Implementation of the Resolution can not be done considering the number of cases that occur or the complicated problems that occur after the issuance of Resolution concerning illegal settlements in Palestine. Although initially the United States as an ally of Israel voted abstained at this resolution, it only sparked enormous anger for Israel and planned to add to the construction of illegal settlements as a real action rejecting the UN Security Council's Resolution on December 23, 2016. The dualism side of the US stance also became a key factor in the impediments to the implementation of UN Security Council resolutions. Where the attitude is inversely proportional shown during the reign of Barack Obama and Donald J. Trump.Keywords: Implementation, Resolution, Illegal Settlements, UN Security Council